Cost-effectiveness of the Self-Help Plus Intervention for Adult Syrian Refugees Hosted in Turkey - Uygun, Ersin (American Medical Association, 2022)
Abstract: Importance: The cost-effectiveness of the Self-Help Plus (SH+) program, a group-based, guided, self-help psychological intervention developed by the World Health Organization for people affected by adversity, is unclear. Objective: To investigate the cost-utility of providing the SH+ intervention combined with enhanced usual care vs enhanced usual care alone for Syrian refugees or asylum seekers hosted in Turkey. Design, Setting, and Participants: This economic evaluation was performed as a prespecified part of an assessor-blinded randomized clinical trial conducted between October 1, 2018, and November 30, 2019, with 6-month follow-up. A total of 627 adults with psychological distress but no diagnosed psychiatric disorder were randomly assigned to the intervention group or the enhanced usual care group. Interventions: The SH+ program was a 5-session (2 hours each), group-based, stress management course in which participants learned self-help skills for managing stress by listening to audio sessions. The SH+ sessions were facilitated by briefly trained, nonspecialist individuals, and an illustrated book was provided to group members. Th intervention group received the SH+ intervention plus enhanced usual care; the control group received only enhanced usual care from the local health care system. Enhanced usual care included access to free health care services provided by primary and secondary institutions plus details on nongovernmental organizations and freely available mental health services, social services, and community networks for people under temporary protection of Turkey and refugees. Main Outcomes and Measures: The primary outcome measure was incremental cost per quality-adjusted life-year (QALY) gained from the perspective of the Turkish health care system. An intention-to-treat analysis was used including all participants who were randomized and for whom baseline data on costs and QALYs were available. Data were analyzed September 30, 2020, to July 30, 2021. Results: Of 627 participants (mean [SD] age, 31.3 [9.0] years; 393 [62.9%] women), 313 were included in the analysis for the SH+ group and 314 in the analysis for the enhanced usual care group. An incremental cost-utility ratio estimate of T£6068 ($1147) per QALY gained was found when the SH+ intervention was provided to groups of 10 Syrian refugees. At a willingness to pay per QALY gained of T£14831 ($2802), the SH+ intervention had a 97.5% chance of being cost-effective compared with enhanced usual care alone. Conclusions and Relevance: This economic evaluation suggests that implementation of the SH+ intervention compared with enhanced usual care alone for adult Syrian refugees or asylum seekers hosted in Turkey is cost-effective from the perspective of the Turkish health care system when both international and country-specific willingness-to-pay thresholds were applied.. © 2022 American Medical Association. All rights reserved.